Study of depressive symptoms according to Zung's self-rating scale on men deprived of freedom in a city of Colombia - C. Vélez-Álvarez; C. Barrera-Valencia; A.V. Benito-Devia; M. Figueroa-Barrera; S.M. Franco-Idarraga
Objective: To assess depressive symptoms in men deprived from freedom in a prison in a Colombian intermediate city. Material and Method: A cross sectional study was performed on a sample of three hundred and three patients in the Medium Security penitentiary and Prison Facility of the city of Manizales between April and May 2014. The information was collected through the Zung self-rating depression scale (SDS), subsequently there were established the positive results for depression screening according to the final score of the scale. Results: 303 men deprived from freedom were evaluated, mean age of 32.96 years +/- 10.8 years, 43.5% were living in cohabitation, 38% were single and 10.2% married; 33.7% had a primary education, 58% had secondary or incomplete secondary education, 5.6% reported higher studies; 38.6% (95% CI: 35.8; 41.4) reported symptoms of depression, predominating in ages between 18 to 44 years, no statistically significant differences p> 0.05 between the variables analyzed were found. Conclusions: The results of this study give rise to clinical evaluation, by specialized staff in the area of psychiatry and his intervention, given the characteristics of self-reported depression for this population.